Multidisciplinary Scientific Cruise to the Northern Mid-Atlantic Ridge and Azores Archipelago - Somoza, Luis (2020)
This work presents the preliminary result of the multidisciplinary cruise EXPLOSEA2 surveying the northern Mid-Atlantic Ridge and Azores Archipelago from 46 300 N to 38 300 N aboard the R/V Sarmiento de Gamboa and ROV Luso over 54 days (June 11 to July 27, 2019). In this cruise report, we detail the geophysical, hydrographic, geological, oceanographic, ecological, and microbiological data acquired and a brief of main findings. The cruise addressed the exploration and comprehensive characterization of venting sites, including the water column, the sediments and rocks that host the hydrothermal activity, and the associated mineralizations, biology, and microbiology. Deep hydrothermal chimneys and massive sulfide deposits (up 3,000 m in depth) within the Moytirra hydrothermal active field were identified on slopes that had not been explored previously. Another striking finding made during the EXPLOSEA2 cruise was the field of carbonate chimneys named the “Magallanes-Elcano” field, a potentially relict ultramafic-hosted hydrothermal site sourced by abiotic methane. This field is related to a serpentinite and gabbro rock outcropping on a dome-shaped massif named the “Iberian Massif.” An outstanding finding of the EXPLOSEA2 survey was the identification of the first garden of soft corals growing after active submarine eruptions were reported in the Azores Archipelago composed by a high density of soft corals the suborder Alcyoniina at the summit and flanks of a recent volcanic cone at 160 m water depth developed during the 1957–1958 eruption of Capelinhos. Several cold-water coral habitats formed by colonial scleractinians (e.g., Lophelia pertusa and Madrepora oculata), coral gardens composed of mixed assemblages of black corals (Leiopathes sp.), and octocorals and dense aggregations of the glass sponge Pheronema carpenteri that may be classified as vulnerable marine ecosystems (VMEs) have been discovered during the EXPLOSEA2 cruise along the northern Mid-Atlantic Ridge. This work reveals the importance of multidisciplinary surveys to the knowledge of deep-sea environments.